Vibration Analysis of a Stripper Cooler Fan through SKF Micro Log Analyzer CMXA 70 – A Case Study at Bhubaneswar Power Plant Limited: Analyzing vibration characteristics and improving balance in an industrial fan (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In-situ balancing is a common balance service for different industries. In-situ balance is a technique for balancing multiple rotary systems as generators, engines, sails, fans and so on in-site. For the vibration observer it really is a challenge to identify the root cause in operating phase or operating mode behind this imbalance.In the work currently underway, an inquiry has been carried out into in situ balancing work of a fan of strippers mounted on the power plant Bhubaneswar limited BPPL. There is still a difference between theoretical and functional conditions. There was an effort to bridge the divide in this initiative. A number of literatures were analysed in conjunction with their experimental measurements on the protocol for the abovementioned balance technique. The void thus detected is to minimise industrial fan vibration. Based on this, the imbalances in industrial fans are diagnosed, accompanied by a flow diagram, to explain them in a simple phase.Different facets of imbalance have been analysed in this study. In fact, on the side of fan drive on the horizontal direction of the plummer block (21,55 mmsec) the fan impeller has considerable displacement and acceleration at the fan and engine locking before any vibration measurements. It indicates imbalance of the fan impeller. SKF CMXA70 Microlog analyzer with an acelerometer on the bearings has been used to collect the vibration results.The project work is validated through suitable procedure to reduce the vibration of industrial fan.